2007
DOI: 10.1002/jor.20421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stimulation via microwave applicator on cartilage matrix gene and HSP70 expression in the rabbit knee joint

Abstract: The objective of this study was to investigate the effects of heat stimulation on the expression of extracellular matrix genes and heat-shock protein 70 (HSP70) in rabbit articular cartilage in vivo. Heat stimulation was applied to the knee joints of Japanese white rabbits for 20 min using a microwave (MW) applicator (2.45-GHz, 0-80 W). After 8-72 h, the articular cartilage was removed from the knee joints and proteins and total RNA were extracted. As controls, knee joints without heat stimulation were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…Heat stimulation regulates T cell proliferation and activation, promotes the priming and activation of dendritic cells, and enhances the migration of Langerhans cells from the epidermis to lymph nodes [9]. It also increases matrix production at cartilage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Heat stimulation regulates T cell proliferation and activation, promotes the priming and activation of dendritic cells, and enhances the migration of Langerhans cells from the epidermis to lymph nodes [9]. It also increases matrix production at cartilage [10].…”
Section: Introductionmentioning
confidence: 99%
“…1,4 In this study, PG was significantly induced by MES þ HS, an effect thought to occur via HSP70. Although col2 increased with HS by microwave without the involvement of HSP70 expression, 1 we found that col2 was not affected by MES þ HS. The differences in the HS method (microwave and heat conduction) might influence the expression of col2.…”
Section: Discussionmentioning
confidence: 55%
“…In recent years, the effectiveness of several drugs, such as chondroitin sulfate and glucosamine, has been reported, but these supplements cannot completely halt the progression of OA. 1 Thus, it is necessary to develop an efficient, safe, and inexpensive therapeutic modality that can prevent cartilage degeneration at the initial stages of OA.…”
mentioning
confidence: 99%
“…This suggests that stimulation at 60 W induces excess stress in chondrocytes, from which cells cannot recover, and that HSP70 serves primarily to protect chondrocytes rather than to promote aggrecan expression. 9 Stimulation at 40 W was therefore assumed to be appropriate in the present study, and the effects of heat treatment at this intensity were evaluated. In the present study, the intraarticular temperature just after heating at 40 W was 38.38C.…”
Section: Discussionmentioning
confidence: 99%
“…While excessive heat stimulation (438C or greater) induced HSP70 expression higher, metabolic activity decreased. 9 MW-induced HSP70 expression therapy at appropriate intensities may therefore be effective.…”
mentioning
confidence: 99%